Understanding the public attitude towards sharks for improving their conservation. (December 2021) - Giovos, Ioannis; Barash, Adi; Barone, Monica; Barría, Claudio; Borme, Diego; Brigaudeau, Cecile; Charitou, Anastasia; Brito, Cristina; Currie, Jock; Dornhege, Mareike; Endrizzi, Lara; Forsberg, Kerstin; et al.
Abstract: Sharks are among the oldest residents of the planet, they possess a unique value as top predators and constitute irreplaceable elements of marine ecosystems. Unfortunately, contemporary narratives widely presented in popular mainstream media have attached an utterly negative connotation to sharks, propagating an unsubstantiated and fabricated image of them as implacable and voracious predators. Recently a lot of attention is devoted to understanding the public perception towards sharks in order to promote their conservation given that a quarter of all shark species are facing extinction. This work assessed the current attitude of the public towards sharks on a global scale, utilizing modern technology through a single protocol that explored the importance of factors like culture, history, or educational level in shaping attitudes. We collected 13, 800 questionnaires from 137 countries, with 25 countries presenting more than 100 answers each, representing in total 92% of the filled questionnaires. A generally positive attitude towards sharks emerged from our study, influenced significantly by several factors including knowledge and participation in marine conservation projects. Interestingly, shark attacks emerged as an important factor, with countries having high numbers of shark attacks exhibiting a highly positive attitude towards sharks, potentially because their citizens are more aware of the issue and the importance of sharks for the marine ecosystems. Guidelines for shifting public attitude towards sharks and consequently advancing shark conservation were also drawn.